SUNNI DAN SYI’AH DALAM HARMONI (Pemikiran M. Quraish Shihab dalam Upaya Rekonsiliasi Ummat) - Ahmad Soleh Sakni (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
The conflict between Sunnis and Shia is not a new problem in the long history of moslem. It is not only focused on the issue of aqidah and worship, but also led to anarchic actions such as those that occur in many places, one of which is Indonesia such as in Madura. M. Quraish Shihab (MQS) Indonesian Muslim scholar, through his endeavor, tried to ensure that these two schools could join hands in living a life shaded by Islamic teachings. MQS tries to unite and make harmony between the two by prioritizing aspects of the similarities between the two streams, not sharpening differences. This was confirmed by M. Quraish Shihab in an expression related to disputes between the two groups,